A multi-institutional assessment of COVID-19-related risk in radiation oncology. (December 2020) - Viscariello, Natalie; Evans, Suzanne; Parker, Stephanie; Schofield, Deborah; Miller, Brett; Gardner, Stephen; Fong de los Santos, Luis; Hallemeier, Christopher; Jordan, Loucille; Kim, Edward; Ford, Eric
Highlights: COVID-19 impact on safety in radiation oncology. Failure modes and effects analysis applied to pandemic response. Examination of how infection control measures impact radiotherapy workflow. Multi-institution study of COVID-19-related practices in radiation oncology departments. Abstract: Purpose: The COVID-19 pandemic has presented challenges to delivering safe and timely care for cancer patients. The oncology community has undertaken substantial workflow adaptations to reduce transmission risk for patients and providers. While various control measures have been proposed and implemented, little is known about their impact on safety of the radiation oncology workflow and potential for transmission. The objective of this study was to assess potential safety impacts of control measures employed during the COVID-19 pandemic. Methods: A multi-institutional study was undertaken to assess the risks of pandemic-associated workflow adaptations using failure mode and effects analysis (FMEA). Failure modes were identified and scored using FMEA formalism. FMEA scores were used to identify highest-risk aspects of the radiation therapy process. The impact of control measures on overall risk was quantified. Agreement among institutions was evaluated. Results: Thirty three failure modes and 22 control measures were identified. Control measures resulted in risk score reductions for 22 of the failure modes, with the largest reductions from screening of patients and staff, requiring use of masks, and regular cleaning of patient areas. The median risk score for all failure modes was reduced from 280 to 168. There was high institutional agreement for 90.3% of failure modes but only 47% of control measures. Conclusions: COVID-related risks are similar across oncology practices in this study. While control measures can reduce risk, their use varied. The effectiveness of control measures on risk may guide selection of the highest-impact workflow adaptions to ensure safe care in oncology.